Construction Cost for Soil Excavation (Cut and Fill) on-Site: Computer Based Program Analysis - Abdelbagi Hamad, Anas Ahmed; Lokman, Azri Ikhwan; Xi, Lim Qian; Fakhrullah, Mohammad Raziq; Zaharin, Nur Iffah; Krishnan, Prakash; Kamil, Nur Atikah; Jeevaragagam, Ponselvi; Ahmad, Faridahanim (Journal of Advanced Industrial Technology and Application, 2021)
Excavation is an important part of nay construction project whereby removing earth to form cavity in the ground. This paper mainly focuses on cut and fill excavation by identify the cost of labor, material and equipment. Besides that, this paper aims to have better understanding on Bill of Quantity using coding. The method implemented for this study is using GNU Octave, version 6.2.0 and manual calculation to calculate the construction cost incurred during excavation process. Referring to the manual calculation, the overall cost obtained for the project is RM 27352.15 whereas using GNU Octave software obtained for the project is RM 27352.15. Thus, both GNU Octave software and manual calculation has zero percent difference. Octave is a computer programme that is designed for numerical computations and able to solve linear and nonlinear mathematical problems.